2021
DOI: 10.3897/evolsyst.5.63674
|View full text |Cite
|
Sign up to set email alerts
|

Beauty is in the eye of the beholder: Cruciform eye reveals new species of direct-developing frog (Strabomantidae, Pristimantis) in the Amazonian Andes

Abstract: We describe a new species of frog from the eastern slopes of the Andes in central Peru. Pristimantis sirasp. nov. has a distinctive crossing mark on the iris and no tympanum. The new species is closely related to P. antisuyu Catenazzi & Lehr, 2018, P. cruciocularis Lehr, Lundberg, Aguilar & von May, 2006, and P. erythroinguinis Catenazzi & Lehr, 2018, but is easily differentiable by lacking colour blotches on groins. Pristimantis sirasp. nov. inhabits the mountain forests from 1550 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Similarly, Chávez et al (2023) described a new species of Scinax from the middle Ucayali River in Peru, S. pyroinguinis . They presented a phylogenetic analysis based on a fragment of the 16S rRNA gene that placed it as the sister taxon of all other species in the S. rostratus group.…”
Section: Note Added In Proofmentioning
confidence: 93%
“…Similarly, Chávez et al (2023) described a new species of Scinax from the middle Ucayali River in Peru, S. pyroinguinis . They presented a phylogenetic analysis based on a fragment of the 16S rRNA gene that placed it as the sister taxon of all other species in the S. rostratus group.…”
Section: Note Added In Proofmentioning
confidence: 93%
“…To compare our newly generated sequence with congeners, we considered sequences of the across Genbank sequences, as well as the outgroup spieces P. buccinator Rodriguez, 1994, and P. sinschi Moravec, Lehr, and Kodejs, 2020, and the new sequences of P. clarae (sequence for the holotype CORBIDI 21664, Genbank Accession Code OQ556784), for a total of 20 terminals. Extraction, amplification, and sequencing of DNA followed standard protocols [10]. We used the 16Sar (forward) primer (5 -3 sequence: CGCCTGTTTAT-CAAAAACAT) and the 16Sbr (reverse) primer (5 -3 sequence: CCGGTCTGAACTCA-GATCACGT) with the following thermocycling conditions (PCR) on a Proflex PCR system (Applied Biosystems, Carlsbad, CA, USA): one cycle of 96 • C/3 min; 35 cycles of 95 • C/30 s, 55 • C/45 s, 72 • C/1.5 min; one cycle 72 • C/7 min.…”
Section: Molecular Analysesmentioning
confidence: 99%
“…A new species of Pristimantis assigned to the Pristimantis danae species Group Padial, Grant and Frost, 2014, having the following combination of characters: (1) Skin on dorsum smooth to shagreen with scattered round and conical tubercles; flanks finely tuberculate; skin on venter weakly areolate or areolate; discoidal fold present or absent and thoracic fold present; dorsolateral folds present; (2) tympanic membrane and tympanic annulus present, distinct; (3) snout short, rounded or truncate in dorsal view and rounded in profile; (4) upper eyelid bearing some low conical tubercles; EW shorter than IOD; cranial crests absent; (5) dentigerous processes of vomers present, distinct, oblique; (6) males with vocal slits and small subgular vocal sac; nuptial pads absent; (7) Finger I shorter than Finger II; discs of digits expanded, truncated; (8) fingers bearing narrow lateral fringes; (9) minute conical ulnar tubercles present or absent and tarsal tubercles present, low, conical; (10) heel bearing one or two low conical tubercles; inner tarsal fold present, weakly defined, short; (11) inner metatarsal tubercle ovoid, prominent, 2 or 3 times as large as outer; outer metatarsal tubercle subconical, distinct; supernumerary plantar tubercles indistinct, scattered; (12) toes bearing narrow lateral fringes; basal toe webbing absent; Toe V longer than Toe III; toe discs slightly smaller than those on fingers; (13) in life (Figure 3), dorsum tan or brown with dark brown marks as a bar or blotch on the top of snout, interorbital bar, a conspicuous canthal stripe, labial bars, supratympanic stripe, triangular blotches on dorsum, diagonal streaks on flanks and diagonal bars on limbs; groins dusty brown with or without scattered cream minute flecks, anterior and posterior surface of thighs dark brown with minute pale cream flecks and with or without some scattered pale cream blotches; ventral surface on throat, belly and hind limbs dirty cream with a dense dark brown mottling, usually with a V-shaped mark below the chin; iris coppery, with the upper half bright and the lower dark, bearing flecks, speckles or vermiculation irradiating from the pupil; sclerotic ring whitish gray; (14) SVL 12.9-15.6 mm (n = 11) in males and 17.6-19.3 mm (n = 2) in females.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Species in the genus are distributed from Central America southwards to southern Brazil and northern Argentina (Frost 2021), occupying a great variety of different biomes in lowland and montane areas. At present, 15 species groups are recognised in the genus (Padial et al 2014;Gonzáles-Durán et al 2017;Páez and Ron 2019;Chávez et al 2021;Zumel et al 2021), but for a majority of species only sparse data are available and these, therefore, remained unassigned to any group (Padial et al 2014). Furthermore, several studies indicated that species diversity in the genus is considerably underestimated by the number of names established, and demonstrated that resolving the taxonomy in this group might be a complex task because of intra-specific polymorphism on the one hand and superficial crypsis on the other (e.g.…”
Section: Introductionmentioning
confidence: 99%